Productivity Optimization of Furniture Company in Inspection Station by using Motion and Time Study Techniques - Talib Bon, abdul; Nadia Abd Karim, hani; Ngadiman, Y.; Nur Aizat Ahmad, ahmad; Abdul Hamid, hadilah (International Journal of Engineering and Technology, 2018)
In the context of in industry, the productivity rate of the company plays an important role in order to maintain the companyâ€™s production. In this study, an approach has been proposed with the aim to improve and optimize the work process on production time, number of processes and production layout using Motion and Time Study technique and some possible solution will be proposed in the end of study. Commonly, many of inspection process has operated manually by workers and caused some of waste in work process such as overproduction, motion and processing. Using Motion and Time Study Technique, the unnecessary motion and time processing will be detected by identify the standard time of each process and ARENA simulation will be applied in order to stimulate and predict the changes in inspection process. Overall, the suggested solution will helps in productivity improvement of the company and cost of production will reduce as well. Â Â